TANTANGAN REGENERASI KEPEMIMPINAN AGAMA HINDU DI DESA SUMBERASRI KABUPATEN BANYUWANGI - Faricha Aulia; Khalid Syaifullah (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
The process of leadership regeneration in Hinduism is an important issue for maintaining the continuity of traditions, ceremonies, and social stability in society. This study examines the Hindu community in Sumberasri Village, Banyuwangi Regency, which faces difficulties in finding successors to religious leaders. The method used in this study is descriptive qualitative through interviews, observation, and document collection. Max Weber's concept of traditional authority is used to analyze the legitimacy of leadership based on culture and ancestral heritage, while Karl Marx's social structure theory analyzes the influence of economic aspects on leadership regeneration. The results of the study reveal three main challenges, namely strict customary regulations, the limited economic conditions of the families of prospective leaders, and the low interest of the younger generation in religious aspects. Social and economic factors have proven to be obstacles in the process of succession of religious leadership, which previously relied heavily on traditional values. This study recommends improving community-based religious education and the active involvement of the younger generation in ritual activities as a strategy to strengthen the process of succession of Hindu leadership in the future. This study recommends improving community-based religious education and actively involving the younger generation in ritual activities as strategies to strengthen the process of Hindu leadership regeneration in the future.